Farmers' preference for farming: Evidence from a nationally representative farm survey in India - Birthal, Pratap S.; Roy, Devesh; Khan, Md. Tajuddin; Negi, Digvijay S. (Wiley, 2015)
Using data from a nationally representative farm survey in India, we have analyzed Indian farmers' stated preference for farming as a profession. Findings show that more than 40% of farmers dislike farming as a profession because of low profits, high risk, and lack of social status, yet they continue with it owing to a lack of opportunities outside agriculture. Farmers who express a preference for moving out of agriculture are mostly those with small landholdings, poor irrigation facilities, fewer productive assets including livestock, and follow a cereal‐centric cropping pattern. They also have relatively lower access to credit, insurance, and information, and are weakly integrated with social networks such as self‐help groups and farmers' organizations. Importantly, the disinclination for farming, conditional on other covariates, is not significantly differentiated by caste, an important indicator of social status in rural India. Yet, within a caste group, the dislike for farming moderates with larger landholdings.